2021
DOI: 10.1007/s11109-021-09734-6
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Social Media Use and Beliefs in Conspiracy Theories and Misinformation

Abstract: Numerous studies find associations between social media use and beliefs in conspiracy theories and misinformation. While such findings are often interpreted as evidence that social media causally promotes conspiracy beliefs, we theorize that this relationship is conditional on other individual-level predispositions. Across two studies, we examine the relationship between beliefs in conspiracy theories and media use, finding that individuals who get their news from social media and use social media frequently e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
104
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 61 publications
8
104
0
Order By: Relevance
“…This phenomenon is also replicated in case of the current COVID-19 pandemic, where most of the conspiracy theories were first generated and disseminated on social media [52,53]. There is also strong evidence that supports a correlation between social media use and beliefs in conspiracy theories [23,51,54], and more specifically, between social media use and beliefs in vaccine and vaccination-related conspiracy theories [34]. A large amount of research [27,30,55] has already demonstrated that shows people who use social media as news or information sources are more prone to believe in COVID-19-related conspiracy theories, including vaccine and vaccination-related conspiracy theories.…”
Section: Conspiracy Theories and Predictors Of Conspiracy Beliefsmentioning
confidence: 60%
See 1 more Smart Citation
“…This phenomenon is also replicated in case of the current COVID-19 pandemic, where most of the conspiracy theories were first generated and disseminated on social media [52,53]. There is also strong evidence that supports a correlation between social media use and beliefs in conspiracy theories [23,51,54], and more specifically, between social media use and beliefs in vaccine and vaccination-related conspiracy theories [34]. A large amount of research [27,30,55] has already demonstrated that shows people who use social media as news or information sources are more prone to believe in COVID-19-related conspiracy theories, including vaccine and vaccination-related conspiracy theories.…”
Section: Conspiracy Theories and Predictors Of Conspiracy Beliefsmentioning
confidence: 60%
“…Additionally, within their social media networks, individuals tend to consume and disseminate ideas and information with which they already agree, without or barely taking into consideration alternative opinions [48,49]. As many scholars have already pointed out, social media plays an essential role in the dissemination of conspiracy theories [50,51]. This phenomenon is also replicated in case of the current COVID-19 pandemic, where most of the conspiracy theories were first generated and disseminated on social media [52,53].…”
Section: Conspiracy Theories and Predictors Of Conspiracy Beliefsmentioning
confidence: 89%
“…This false positive error, combined with confirmation bias and hindsight bias, allow for conspiracy theorists to assert an existing pattern - in this case, mobile electromagnetic frequencies - and reassign its sinister effect from surveillance to the spread of COVID-19. However, Enders et al (2021) found that the impact of social media on such is a form of biased assimilation. Conjunction fallacies are errors of probabilistic reasoning where people overdetermine the prospect of co-occurring phenomenon ( Enders and Smallpage, 2019 ).…”
Section: Conspiracy Theories and Statistical Fallaciesmentioning
confidence: 99%
“…An Oxford Survey found that 40% of respondents believed “to some extent the spread of the virus is a deliberate attempt by powerful people to gain control” ( OCEANS, 2020 ) and only 64% are sure they will take the vaccine ( Sherman et al, 2020 ). An American study, by contrast, found that only 11% of respondents agreed 5G and COVID were correlated ( Enders et al, 2021 , p. np). The 5G-COVID-19 conspiracy theory arrives in a context of growing scepticism over public health institutions and measures.…”
Section: Introductionmentioning
confidence: 99%
“…Although out of scope for the present paper, it is worth noting that useful work has examined the role of social networks and the proliferation of misinformation and conspiracy theories online [3][4][5]. Such literature examines the processes of how hateful or false information is spread.…”
Section: Introductionmentioning
confidence: 99%